1983
DOI: 10.1073/pnas.80.11.3250
|View full text |Cite
|
Sign up to set email alerts
|

Cloning of the gene for C protein, a low molecular weight spore-specific protein from Bacillus megaterium.

Abstract: The structural gene for C protein, a low molecular weight spore-specific protein from Bacilus megaterium, has been cloned in Escherichia coli. Expression of the C-protein gene in E. coli requires an external transcription promoter and prevention of termination of transcription prior to transcription of all or part of the sequence coding for the C protein. The gene for the C protein is within a 5-kilobase DNA fragment, but this fragment does not code for either of the other two major low molecular weight spore … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
36
0

Year Published

1985
1985
1989
1989

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 19 publications
(37 citation statements)
references
References 25 publications
1
36
0
Order By: Relevance
“…The sources of all B. subtilis and Escherichia coli strains used have been described previously (1,3,4,5,8), with the exception of the bacteriophage X gtlO host E. coli POP-138, which was obtained from R. Davis (Stanford University, Stanford, Calif.). The source of M13 phage, the pUC plasmids, and plasmid pMC13 carrying the B. subtilis sspC gene were also described previously (3, 9); X gtlO was also obtained fom R. Davis, and plasmid pJH101 (7) was obtained from J. Hoch (Scripps Clinic, La Jolla, Calif.).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The sources of all B. subtilis and Escherichia coli strains used have been described previously (1,3,4,5,8), with the exception of the bacteriophage X gtlO host E. coli POP-138, which was obtained from R. Davis (Stanford University, Stanford, Calif.). The source of M13 phage, the pUC plasmids, and plasmid pMC13 carrying the B. subtilis sspC gene were also described previously (3, 9); X gtlO was also obtained fom R. Davis, and plasmid pJH101 (7) was obtained from J. Hoch (Scripps Clinic, La Jolla, Calif.).…”
Section: Methodsmentioning
confidence: 99%
“…B. subtilis chromosomal DNA was isolated and purified as described previously (3). Plasmid or chromosomal DNA was isolated from cells grown overnight in L broth plus 0.5% glucose with appropriate drugs (ampicillin [50 jig/ml], tetracycline [10 ,ug/ml], or chloramphenicol [10 ,ug/ml for E. coli strains, 5 ,ug/ml for B. subtilis strains] as needed) as previously described (4,5) and purified by CsCl gradient centrifugation if necessary. X gtlO derivatives were grown on E. coli POP-138, and phage were grown and phage DNA was isolated as described by Davis et al (6).…”
Section: Methodsmentioning
confidence: 99%
“…DNA fragments were separated by agarose gel electrophoresis, and individual fragments were isolated as previously described (5). The 0.65-kilobase (kb) MboI fragment containing the coding sequence of the B. megaterium SASP-B gene was also isolated as previously described (9).…”
Section: Methodsmentioning
confidence: 99%
“…B. subtilis DNA (50 ,ug) was digested with EcoRI and PvuII and run on a 1% agarose gel, and the DNA in regions of the gel containing fragments ranging in size from 1.0 to 1.8 and 3.5 to 5 kb was isolated as previously described (5). EcoRI linkers were added to the purified DNA, the samples were digested with EcoRI, and linker fragments were removed by spermine precipitation (11).…”
Section: Methodsmentioning
confidence: 99%
“…We decided to use this approach for two reasons. (i) Previous work had strongly suggested that SASP genes would not be transcribed in Escherichia coli from their own promoters (4,14), and (ii) several SASP genes, even if transcribed in E. coli, are either translated very poorly or the final protein is unstable (3,7,9,14). DNA (17).…”
mentioning
confidence: 99%